C++ basics - Knowlton, Todd, 1966- (Cincinnati, Ohio : South-Western Computer Education, 2000)
This book introduces readers to programming computers using a language called C++: Data and Operations; Strings and Screen, Input and Output; Decision making and loops; Functions; Arrays, Data files, and Object-oriented programming.
Keywords: C++.; Computer program language; C++ (Computer program language)